Geary's contiguity ratio - Unwin, Antony (Economic & Social Studies, 1996)
Forty years ago Geary published a paper oil spatial statistics introducing the contiguity ratio, c, to measure spatial pattern. He discussed c not only as a direct measure but as a regression diagnostic for assessing spatial association amongst regression residuals, c has continued to be used and this paper describes its properties, its current status and how work in this area has developed, emphasising particularly the complementary new approaches offered by interactive graphics tools.
Keywords: Contiguity ratio; Statistical methods